Lifespan and healthspan benefits of exogenous H2S in C. elegans are independent from effects downstream of eat-2 mutation - Li Theng Ng; Li Fang Ng; Richard Ming Yi Tang; Diogo Barardo; Barry Halliwell; Philip Keith Moore; Jan Gruber (npj Aging and Mechanisms of Disease, 2020)
Abstract Caloric restriction (CR) is one of the most effective interventions to prolong lifespan and promote health. Recently, it has been suggested that hydrogen sulfide (H2S) may play a pivotal role in mediating some of these CR-associated benefits. While toxic at high concentrations, H2S at lower concentrations can be biologically advantageous. H2S levels can be artificially elevated via H2S-releasing donor drugs. In this study, we explored the function of a novel, slow-releasing H2S donor drug (FW1256) and used it as a tool to investigate H2S in the context of CR and as a potential CR mimetic. We show that exposure to FW1256 extends lifespan and promotes health in Caenorhabditis elegans (C. elegans) more robustly than some previous H2S-releasing compounds, including GYY4137. We looked at the extent to which FW1256 reproduces CR-associated physiological effects in normal-feeding C. elegans. We found that FW1256 promoted healthy longevity to a similar degree as CR but with fewer fitness costs. In contrast to CR, FW1256 actually enhanced overall reproductive capacity and did not reduce adult body length. FW1256 further extended the lifespan of already long-lived eat-2 mutants without further detriments in developmental timing or fertility, but these lifespan and healthspan benefits required H2S exposure to begin early in development. Taken together, these observations suggest that FW1256 delivers exogenous H2S efficiently and supports a role for H2S in mediating longevity benefits of CR. Delivery of H2S via FW1256, however, does not mimic CR perfectly, suggesting that the role of H2S in CR-associated longevity is likely more complex than previously described.